The Conflict Of Interest About Gender Paradigm In West Sumatera - Fahmi, Reza (Ar Raniry : International Journal of Islamic Studies, 2015)
The Minangs are the world's largest matrilineal society; properties such as land and houses are inherited through female lineage. Some scholars argue that this might have caused the diaspora(Minangkabau, "merantau") of Minangkabau males throughout the Maritime Southeast Asia to become scholars or to seek fortune as merchants. However, the native Minangkabaus agreed that this matrilineal culture is indeed the result of (not the reason for) diaspora. With their men travelling out of the country for unspecified time (with possibility of some of them not returning home), it is only logical to hand the land and property to those who do not have to leave it: The women. This also ensures the women's (meaning: mothers of the future generations') welfare and hence ensuring their offsprings welfare. Besides, native MinangKabaus argue that "Men can live anywhere and hence they do not need a house like women do".Ã‚Â Abstrak: Masyarakat Minangkabau merupakan masyarakat matrilineal terbesar di dunia; di mana kepemilikan seperti tanah dan rumah diwariskan melalui garis keturunan ibu. Beberapa ilmuan masih berdebat dikarenakan diaspora (Minangkabau,Ã‚Â  Ã¢â‚¬Å“merantauÃ¢â‚¬Â) dari lelaki Minang ke berbagai daerah di wilayah Asia tenggara sebagai usaha untuk mencari keuntungan melalui kegiatan perdagangan. Walau bagaimanapun, masyarakat asli Minangkabau sependapat bahwa, budaya matrilinial menjadi penyebab utama diaspora tersebut. Dengan bepergiannya para kaum pria untuk merantau dalam jangka waktu yang tidak dapat dipastikan (bahkan terkadang mereka tidak pulang kampung), itu lebih disebakan oleh ketiadaan kepemilikan tanah dan rumah yang telah dijelaskan di atas. Inu juga dapandang sebagai masa depan sebuah generasi. Selanjutnya ada pandangan bahwa, lelaki. dapat hidup atau tinggal di mana saja dan mereka tidak membutuhkan rumah seperti kaum perempuan yang membutuhkannya.